2022
DOI: 10.1021/acsomega.2c01281
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antioxidant, Antiviral, and Anticancer Activities of the Extract of Fermented Egyptian Rice Bran Complexed with Hydroxypropyl-β-cyclodextrin

Abstract: Egyptian rice bran was fermented with baker’s yeast, and released phenolics were extracted with aqueous methanol to give fermented rice bran extract (FRBE). The analysis of the FRBE with ultra-performance liquid chromatography–electrospray ionization–tandem mass spectrometry revealed 21 compounds, mainly phenolic acids and flavonoids. The FRBE was then complexed with (2-hydroxypropyl)-β-cyclodextrin (HPβCD) via noncovalent host–guest inclusion complexation using the thin-film hydration technique to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Supramolecular macrocyclic nanosystems, including calix­[ n ]­arenes, cyclodextrins, pillar­[ n ]­arenes, cucurbit­[ n ]­urils (CBs), etc. , have shown dynamic regulation characteristics and multifunctional properties. The structure of macrocyclic compounds can be altered in response to various external stimuli (temperature, pH, light, etc. ) thus controlling the release of their loaded guest molecules .…”
Section: Supramolecular Nanovesicles For Cancer Targeted-deliverymentioning
confidence: 99%
“…Supramolecular macrocyclic nanosystems, including calix­[ n ]­arenes, cyclodextrins, pillar­[ n ]­arenes, cucurbit­[ n ]­urils (CBs), etc. , have shown dynamic regulation characteristics and multifunctional properties. The structure of macrocyclic compounds can be altered in response to various external stimuli (temperature, pH, light, etc. ) thus controlling the release of their loaded guest molecules .…”
Section: Supramolecular Nanovesicles For Cancer Targeted-deliverymentioning
confidence: 99%
“…Also the survival rates were best for NP-treated mice with 50 days' life as compared to 41 days for plain PTX (Yuan et al, 2016). Fahmy et al (2022) explored the properties of fermented Egyptian rice bran extract (FRBE) for their anticancer and antioxidative characteristics. Solubility and bioavailability of the phenolic chemical compounds found in the extract was improved after it was complexed with HP-β-CD using the thin-film hydration method.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Thus, phytochemicals developed from natural extracts are recognized as a promising source of more effective and safer anticancer drugs than synthetic ones. Several studies have reported the potential applications of phytochemicals in cancer therapy [ 9 , 10 , 11 ], such as Peganum harmala L. seeds extract [ 12 ], [ 13 ], betaine (extracted from wheat germ and spinach) [ 14 ], fermented Egyptian rice bran ( Oryza sativum ) [ 15 ], and ozonated olive oil [ 16 ]. In addition, psoralidin (Ps) is a natural phenolic coumarin phytochemical ( Figure 1 ) extracted from the seeds of Psoralea corylifolia L. grown in various areas in India, Europe, and Asia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%